FRACTIONAL WAVELET ANALYSIS OF MECHANICAL STRESSES IN COMPOSITE PLATES - Pysarenko , Oleksandr (Collection of scientific papers «ΛΌГOΣ», 2024)
Damage assessment in polymer and composite structures can be carried out using a wide range of structural diagnostics methods, which include thermography, ultrasound and radiographic methods, etc. One of the most promising methods is the vibration method, which meets the basic requirements for testing procedures, namely, it must be non-destructive and, if possible, non-invasive [1]. Methods of this type should ensure the detection, localization and identification of various types of damage at the earliest possible stage.